"Feel Supported and not Alone": A Qualitative Study of Supports Needed by Pregnant Women in Preventing Anemia - Arifah, Izzatul; Shabrina Ramadhani, Nur; Kusumawati, Yuli; Setiawan, Arif (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: The ability of pregnant women to prevent anemia is influenced by their social environment support, such as family, husband, or health workers. However, it has not been known which sources of support are preferred and needed by pregnant women. Aims: This study aims to explore the support preferred and needed by pregnant women in preventing anemia. Methods: This study was qualitative research with a case study approach. Semi-structured interviews were conducted with 18 pregnant women at the gestational age starting from 16 weeks who had pregnancy checks at the Sangkrah, Kratonan, and Gilingan Primary Healthcare Centers, Surakarta City. Informants were obtained through a purposive sampling technique. This study used thematic data analysis. Results: Three emerging themes from this study include 1) pregnant women's perceived ability and motivation to prevent anemia; 2) the support needed to prevent anemia; and 3) information technology support for preventing anemia. Some women felt difficulties preventing anemia, especially in consuming IFA tablets and nutritious food; feeling supported and not alone was the motivation to prevent anemia. The most preferred support was from the husband, and the next was health workers. Pregnant women welcome an application with some features to support preventing anemia. Conclusions: Support from husband and health workers is the most preferred. Pregnant women perceive the benefits of using applications that support anemia prevention. It is necessary to develop applications that integrate support from husbands and health workers to create good conditions that enable and motivate pregnant women to practice anemia prevention behavior.